2015
DOI: 10.1556/aphysiol.102.2015.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of creatine malate supplementation on physical performance, body composition and selected hormone levels in spinters and long-distance runners

Abstract: Purpose: The aim of the study was to determine whether creatine malate (CML) supplementation results in similar ergogenic effect in sprinters and long-distance runners. The other goal was to compare changes in body composition, physical performance and hormone levels after six-week training in athletes, divided into subgroups supplemented with creatine malate or taking placebo. Results: Six-week supplementation combined with physical training induced different effects in athletes. Significantly higher increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
(31 reference statements)
1
11
0
Order By: Relevance
“…The participants had an average age of 20.1 ± 0.2 years and had engaged in track and field events for an average of 7.8 ± 0.3 (range, 4-11) years. As expected from previous studies (28,29), the sprinters had a significantly higher body weight, body mass index, and lean mass and body fat compared with endurance runners (P < 0.05). There were no significant differences between endurance runners vs. sprinters for absolute intake of energy (2,387 ± 85.5 vs. 2,209 ± 136 kcal/day; P = 0.34), protein (81.3 ± 3.7 vs. 81.9 ± 5.7 g/day; P = 0.94), fat (68.7 ± 4.3 vs. 64.3 ± 4.2 g/day; P = 0.48), carbohydrates (336.6 ± 11.5 vs. 311.6 ± 25.0 g/day, P = 0.45), and iron (8.1 ± 2.0 vs. 8.6 ± 3.0 mg/day; P = 0.64).…”
Section: Resultssupporting
confidence: 88%
“…The participants had an average age of 20.1 ± 0.2 years and had engaged in track and field events for an average of 7.8 ± 0.3 (range, 4-11) years. As expected from previous studies (28,29), the sprinters had a significantly higher body weight, body mass index, and lean mass and body fat compared with endurance runners (P < 0.05). There were no significant differences between endurance runners vs. sprinters for absolute intake of energy (2,387 ± 85.5 vs. 2,209 ± 136 kcal/day; P = 0.34), protein (81.3 ± 3.7 vs. 81.9 ± 5.7 g/day; P = 0.94), fat (68.7 ± 4.3 vs. 64.3 ± 4.2 g/day; P = 0.48), carbohydrates (336.6 ± 11.5 vs. 311.6 ± 25.0 g/day, P = 0.45), and iron (8.1 ± 2.0 vs. 8.6 ± 3.0 mg/day; P = 0.64).…”
Section: Resultssupporting
confidence: 88%
“…Information about the incidence of adverse effects was not included in this study investigating an intake of 5 g tricreatine malate per day for 6 weeks in young men during judo training . In another study, an elevation of growth hormones in male sprinters (but not in long‐distance runners) was observed after supplementation of around 5 g tricreatine malate per 70 kg lean body mass for 6 weeks .…”
Section: Safety Of Creatine Formsmentioning
confidence: 99%
“…It is a known fact that more than fifty cosmetic products contain malic acid [10,11]. Recent studies have shown that keratin-malate supplementation can be used as a performance-enhancing agent and increases the physical performance of athletes [12]. It has been investigated that a diet high in malic acid, which is the precursor of citrate, increases kidney stone formation [13].…”
Section: Introductionmentioning
confidence: 99%